The role of supply chain sustainability in strengthening the business competitiveness - Kitrish, E. (Економічний вісник Донбасу, 2016)
Management of enterprises as well as their investors and other stakeholders are increasingly concerned about the potential risks posed to a company by the activities within its supply chain. In a modern networked economy, the contracting process, and measures to ensure the sustainability of relations with suppliers form the necessary strong coupling, which ensures the integrity of all links in the value chain. The efforts aimed on introducing modern system of supply chains management in business practice are important especially for industrial enterprises of countries with developing market economics due to weak institutional framework for doing business. For many Ukrainian enterprises, acuteness of this issue is increasing significantly in the current conditions when they are pushed to reorient at new markets of raw materials and sales of their products. Attempt to generalize modern approaches to management of supply chains, which ensure the sustainability of a business and thus strengthen its competitiveness, and to identify ways how to facilitate the implementation of these approaches in the management practices of Ukrainian enterprises is made in the paper. Менеджери підприємств, а також їх інвестори та інші зацікавлені сторони все більше стурбовані потенційними ризиками, що пов'язані з діяльністю компанії в межах її ланцюгів постачань. У сучасній мережевій економіці, процес укладання контрактів, а також заходи щодо забезпечення стійкості відносин з постачальниками формують необхідний сильний зв'язок, який забезпечує цілісність всіх ланок в ланцюжку створення вартості. Зусилля, спрямовані на введення сучасної системи управління ланцю- гами постачань в діловій практиці мають важливе значення, особливо для промислових підприємств країн з ринковою економікою, що розвивається, через слабкі інституційні основи для ведення бізнесу. Для багатьох українських підприємств гострота цього питання значно зростає в сучасних умовах, коли вони вимушені переорієнтовуватися на нові ринки сировини і збуту своєї продукції. Дана стаття є спробою узагальнити сучасні підходи до управління ланцюгами постачань, які забезпечують стійкість бізнесу і тим самим зміцнюють конкурентоспроможність підприємства, а також визначити способи, як сприяти реалізації цих підходів в управлінській практиці українських підприємств. Менеджеры предприятий, а также их инвесторы и другие заинтересованные стороны все больше обеспокоены потенциальными рисками, связанными с деятельностью компании в пределах ее цепей поставок. В современной сетевой экономике, процесс заключения контрактов, а также меры по обеспечению устойчивости отношений с поставщиками формируют необходимую сильную связь, которая обеспечивает целостность всех звеньев в цепочке создания стоимости. Усилия, направленные на введение современной системы управления цепочками поставок, в деловой практике имеют важное значение, особенно для промышленных предприятий стран с развивающейся рыночной экономикой из-за слабых институциональных основ для ведения бизнеса. Для многих украинских предприятий, острота этого вопроса значительно возрастает в современных условиях, когда они вынуждены переориентироваться на новые рынки сырья и сбыта продукции. Данная статья является попыткой обобщить современные подходы к управлению цепями поставок, которые обеспечивают устойчивость бизнеса и тем самым укрепляют конкурентоспособность предприятия, а также определить способы, как способствовать реализации этих подходов в управленческой практике украинских предприятий.